2011
DOI: 10.1111/j.1751-1097.2011.00919.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Binding of BODIPY‐GTP by the Photosensory Protein YtvA from the Common Soil Bacterium Bacillus subtilis

Abstract: The YtvA protein, which is one of the proteins that comprises the network carrying out the signal transfer inducing the general stress response in Bacillus subtilis, is composed of an N-terminal LOV domain (that binds a flavin [FMN]) and a C-terminal STAS domain. This latter domain shows sequence features typical for a nucleotide (NTP) binding protein. It has been proposed (FEBS Lett., 580 [2006], 3818) that BODIPY-GTP can be used as a reporter for nucleotide binding to this site and that activation of the LOV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 35 publications
2
13
0
1
Order By: Relevance
“…After addition of YtvA or YtvA-STAS to the fluorophore solution the relative fluorescence was significantly increased. This is in agreement with the results presented in the literature so far [25], [29]. Since BODIPY is very hydrophobic, however, interactions of BODIPY with hydrophobic regions on the protein surface could be the reason for binding.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…After addition of YtvA or YtvA-STAS to the fluorophore solution the relative fluorescence was significantly increased. This is in agreement with the results presented in the literature so far [25], [29]. Since BODIPY is very hydrophobic, however, interactions of BODIPY with hydrophobic regions on the protein surface could be the reason for binding.…”
Section: Resultssupporting
confidence: 93%
“…This assay has since been used to study the effect of mutations on the activation mechanism in YtvA [25][28]. More recently, however, Nakasone et al could not confirm that GTP binds to YtvA but found that the fluorescence labeled GTP analog (BODIPY-GTP) used in the assays binds unspecifically to YtvA [29]. The aim of the investigations described here was originally to determine the precise binding site for GTP on YtvA using heteronuclear NMR.…”
Section: Introductionmentioning
confidence: 99%
“…3A) by assessing the impact of directed mutagenesis on in vivo activation of B [20] and by assessment of alterations in 4-bora-3a,4a-diaza-s-indacene (BODIPY)-GTP TR fluorescence enhancement [21]. However, a recent report indicates that some recombinant YtvA LOV constructs lacking the STAS domain similarly enhance BODIPY-GTP TR fluorescence in a manner insensitive to competition by added nucleotide triphosphates, but suggestive of predominant actions of the hydrophobic BODIPY moiety [25]. In addition, GTPase activity of the STAS domain has not yet been detected.…”
Section: Stas Domains In Bacterial Anion Transport Proteins: Bica Rvmentioning
confidence: 99%
“…3A). Studies demonstrating YtvA STAS domain-mediated enhancement and red-shift of BODIPY TR -GTP fluorescence in the illuminated state, with further slight enhancement and redshift during thermally driven recovery in the dark [24,22] have suggested a guanine nucleotide binding function of the STAS domain with conformational sensitivity to FMN-suggest that the light-induced conformational change may be more modest than depicted in this schematic drawing [25].…”
mentioning
confidence: 99%
“…Кроме того, фотоактивиро-ванный YtvA in vivo действует как положительный регулятор транскрипционного фактора общего стресса σB [23]. Поскольку мутации, нарушающие связывание ГТФ в STAS-домене или междоменное распространение светоиндуцированного сигнала в фоторецепторе, подавляют активированную синим светом σB-зависимую транскрипцию in vivo, счита-ется, что связывание ГТФ необходимо для прояв-ления функциональной активности YtvA [23][24][25].…”
Section: регуляторные функции Bluf-и Lov-фоторецепторовunclassified